Quality in Colonoscopy: Beyond the Adenoma Detection Rate Fever - Taveira,Filipe (2017)
Background: Colonoscopy quality is a hot topic in gastroenterological communities, with several actual guidelines focusing on this aspect. Although the adenoma detection rate (ADR) is the single most important indicator, several other metrics are described and need reporting. Electronic medical reports are essential for the audit of quality indicators; nevertheless, they have proved not to be faultless. Aim: The aim of this study was to analyse and audit quality indicators (apart from ADR) using only our internal electronic endoscopy records as a starting point for improvement. Methods: An analysis of electronically recorded information of 8,851 total colonoscopies from a single tertiary centre from 2010 to 2015 was performed. Results: The mean patient age was 63.4 ± 8.5 years; 45.5% of them were female, and in 14.6% sedation was used. Photographic documentation was done in 98.4% with 10.7 photographs on average, and 37.4% reports had <8 pictures per exam. Bowel preparation was rated as adequate in 67%, fair in 27% and inadequate in 4.9% of cases. The adjusted caecal intubation rate (CIR) was 92%, while negative predictors were inadequate preparation (OR 119, 95% CI 84-170), no sedation (OR 2.39, 95% CI 1.81-3.15), female gender (OR 1.61, 95% CI 1.38-1.88) and age ≥ 65 years (OR 1.56, 95% CI 1.34-1.82). In 28% of patients, a snare polypectomy was performed, correlating with adequate preparation (OR 5.75, 95% CI 3.90-8.48), male gender (OR 1.82, 95% CI 1.64-2.01) and age ≥ 65 years (OR 1.25, 95% CI 1.13-1.37; p < 0.01) as positive predictors. An annual evolution was observed with improvements in photographic documentation (10.7 vs. 12.9; p < 0.001), CIR (91 vs. 94%; p = 0.002) and adequate bowel preparation ( p = 0.004). Conclusions: There is much more to report than the ADR to ensure quality in colonoscopy practice. Better registry systematization and integrated software should be goals to achieve in the short term.